Bio-inspired and Bio-mimetic materials - an overview - Bhuvaneshwari, B.; Palani, G. S.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
The vital role of bio-inspired and bio-mimicking concepts in the technological trends towards the sustainability is a key factor for all type of interdisciplinary research, such as biomedical, electronics, composites, ceramics, to name a few. The general view of these materials on various applications as mentioned above and some specific application in civil engineering field depicts the inspiration of bio-process into the product technology. This paper presents an overview on importance of bio-inspired and biomimetic materials towards bridging of communication gap between science and engineering. The review includes the role of bio-inspired materials in various fields in general followed by an outlook to areas of possible engineering applications. Along with this, most important nano materials namely natural nano mineral - clay, natural polymer- cellulose, and biomimitic material -calcium carbonate are critically reviewed. The methodology of fine tuning of these materials to meet the functional requirements of construction sector has been discussed. The application of computational and theoretical materiomics towards simulation of the behaviour of bio-inspired materials has also been covered. One of the main bio-inspired process such as bio-mineralization in the field of civil engineering discussed in detail. A complete spectrum on topographic (structural) changes of materials and their emerging trends and needs for the futuristic development of new construction materials can be arrived based on the discussions in paper. It is concluded that the basic principles and role of bio-inspired materials in various aspects such as materials property and their novel applications, multi scale approaches as well as continuum theory provide a development of new generation of intelligent materials from nano to macro scales.